A new species of Chthonerpeton (Amphibia: Gymnophiona: Typhlonectidae) from Bahia, Brazil - Da Silva, Hélio Ricardo; de Britto-Pereira, Mônica Cox; Caramaschi, Ulisses (Zootaxa, 2003)
A new species of the Chthonerpeton indistinctum group is described from Brazil based on fourteen specimens collected in the Municipality of Conde, State of Bahia. The new species is characterized by 94–103 primary annuli, 100–108 vertebrae, tentacular aperture closer to nares than to eyes, umpigmented cloacal disk and narial plug areas, and by the number of vomeropalatine and dentary teeth that is smaller than that of the other species in the group. The new species is aquatic and fossorial, and can be found swimming actively at night or borrowed in mud in places near the river.